Besinning oor die apostolaat in die Nederduitsch Hervormde Kerk - Westhuizen, H. G. van der (Hervormde teologiese studies, 1990)
A considering on the apostolate of the Nederduitsch Hervormde Church In spite of spending large sums on missions, the Nederduitsch Hervormde Kerk van Afrika needs to rethink the organisation of its mission councils. A plea is made for fundamental reorientation at membership level in both the Nederduitsch Hervormde Kerk van Afrika as the ‘missionary church’ and the Hervormde Kerk in Suidelike Afrika as the ‘mission church’ in respect of their mission structures.